The Spartan Lysander’s ‘métis’ representation in the Battle of Aegospotami (405 BC) - Assumpção, Luis Filipe (Romanitas - Revista de Estudos Grecolatinos, 2019)
In this study, we will assess Lysander’s metis/cunning representation in Xenophon’s speech and the assumptions that ensured the Peloponnesian Confederation victory. To meet this objective, the Discourse Analysis method proposed by Dominique Maingueneau was applied, thus overcoming the superficiality of the text. The Peloponnesian War (431-404 BC) was one of the most striking events discussed in ancient literature, due to its social impact. After approximately twenty-seven years of war, the poleis involved in this conflict became depleted of resources. In this context, it is worth noting that the Spartiate Lysander - using Persian wealth - built a unique combat strategy to defeat the Athenians in the battle of Aegospotami, without engaging in direct sea combat, in 405 BCE. Thus, Lysander’s metis/cunning was represented in the literary discourse of Antiquity as the fundamental mechanism for the end of the Peloponnesian War.